EVOLUSI IJTIHAD IMAM SYAFI’I : Dari Qawl Qadīm ke Qawl Jadīd - Ainol Yaqin (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2016)
This article describes Imam al-Shāfi'i thought in building istinbath Islamic law method and its decition's which evolved from qawl qadīm to qawl jadīd. He is known as the founder of uṣūl al-fiqh science which is arranged systematically-logically and critically. He tried to combine the two schools of thought, those are: Maliki, known as ahl al-ḥadīth that thrives in the Hijaz, and the Hanafi, known as ahl al-ra'y that is entrenched in Iraq. He managed to combine the two schools by taking method good ahl al-ḥadīth and leaving the less ones successfully. Reciprocally, he took the good ahl al-ra’y method and left the poor. It was done for the reason that he had studied with Imam Malik and Muḥammad ibn Ḥasan al-Shaibani, the adherents of the Hanafi schools. The fatwa which he formulated at his living in Iraq is known as qawl qadīm. After he reviewed the fatwa built in Iraq and found the fragility of the arguments as a fundamental, finally, he triggered a new law, namely qawl jadīd which was based on the strong arguments.